Osteogenesis imperfecta: cesarean deliveries in identical twins. Issue 1 (February 2015) - Dinges, E.; Ortner, C.; Bollag, L.; Davies, J.; Landau, R.
Highlights Patients with severe osteogenesis imperfecta are mostly delivered by cesarean section. Both general and neuraxial techniques have been successful for cesarean anesthesia. Individual patient characteristics should be used to determine mode of anesthesia.